PHOSPHATE VALORIZATION BY DRY CHLORINATION ROUTE - Kanari, Ndue (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
This work deals with the extraction of phosphorus chlorinated compounds from phosphate materials using chlorination with gaseous chlorine. An industrial sample of dicalcium phosphate dihydrate, after transformation into calcium pyrophosphate (Ca2P2O7), is subjected to reactions with Cl2+CO+N2 and Cl2+C+N2 at temperatures ranging from 625 to 950 °C using boat experiments. Gathering results of the thermodynamic predictions and TG/DT analysis with those of SEM and XRD examinations of the chlorinated residues allowed the interpretation of phenomena and reactions mechanism occurring during the calcium pyrophosphate carbochlorination. Reaction rate of Ca2P2O7 by Cl2+CO+N2 at 950 °C is slowed down due to the formation of a CaCl2 liquid layer acting as a barrier for the diffusion of the reactive gases and further reaction progress. While, the carbochlorination with Cl2+C+N2 led to almost full chlorination of Ca2P2O7 at 750 °C and the process proceeds with an apparent activation energy of about 104 kJ/mol between 625 and 750 °C. Carbochlorination technique can be considered as an alternative and selective route for the valorization of low grade phosphates and for the phosphorus extraction from its bearing materials.